Sustainability Analysis of Gallus Gallus Domesticus Poultry at The Jago Karah Farm Community, Surabaya - Nia Amalia; Sri Widayanti; Mirza Andrian Syah (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The complexity of urban livestock poultry issues, such as higher demand for eggs than supply, rising feed prices, densely populated locations with limited land, several members leaving the community, and the suboptimal use of technology, can have an impact on the sustainability of poultry. This study aims to evaluate the sustainability status of Gallus gallus domesticus poultry at the JKF Community based on ecological, economic, social, technological, and institutional dimensions. The analytical method used is Multi-Dimensional Scaling (MDS) through the Rapid Appraisal of the Status of Poultry (Rap-Poultry) approach. The analysis results show that the ecological dimension has a sustainability score of 72.28, the economic dimension 51.78, the social dimension 69.60, the technological dimension 51.03, and the institutional dimension 78.21. The overall sustainability score of Gallus gallus domesticus poultry is 64.97. The sustainability status of Gallus gallus domesticus poultry in the JKF Community is categorized as moderately sustainable, with the ecological, economic, social, and technological dimensions also considered moderately sustainable. In contrast, the institutional dimension is classified as highly sustainable.